A novel observation method for determining the crack stress thresholds of rock based on Hooke's law. Issue 12 (23rd August 2020) - Du, Ruifeng; Pei, Xiangjun; Jia, Jun; Zhang, Xiaochao; Gao, Meiben; Li, Tiantao; Zhang, Guohua
Abstract: The crack stress thresholds of rocks have remained a focus in rock mechanics and engineering. Herein, a novel observation method uses Hooke's law to evaluate crack stress thresholds based on transition points in the equivalent elastic modulus. Unlike previous studies, this method considers confining pressure as a variable and involves a differential method to handle the variation of discrete data. To test the method, we compare it with the volumetric strain method and another observation method with respect to the crack stress thresholds of sandstone and granite. The results are within the boundary values presented in the literatures. For the sandstone and granite samples, the proposed method performs better than the other two methods. In summary, the results indicate that the proposed method can be practically applied with that a promising performance. In the future, we will further improve the method by considering more types of rocks with various confining pressures.